ROLE OF THE NURSE AUDITOR: OBJECTIVITY, LEGISLATION AND ETHICS (Fiep Bulletin - online, 2015)
Aim: to build an analytical and multidisciplinary text, with approach on concepts, tools of work, profile and legislation relevant to the work of the auditor nurse. It was composed of a bibliographical research of arguments, where it was extracted which models of auditing in complementary services in private health care, and the relationship of these with nursing sectors, highlighting ethical, legal, economic and interventional aspects. It was discussed the rights of the users and operators of health plans and analyzed contributors who collaborate on building guidelines to these institutions and the workers involved in them, especially nurses. Having the interventionist bioethics as a basis, reports on the practice of nursing audits were presented, highlighting the articulation between the citizen and human rights and between patients' rights and duties of users and health workers. These reports aimed to assist these workers in their learning, and to promote changes in their practices. Some textual manifestations about the profile and performance of the auditor nurses were reflexively commented. It was verified that, despite the relevance of the theme and the creation of specialized courses in this area, there is still scarcity of the scientific production within and outside academia. It was concluded that there is need for greater scientific and socio-cultural encouragement with expansion of skills in this sector, since it is very promising for the maintenance and reproduction of skilled workforce in nursing auditing, as well as to improve the quality assistance and social control in health.
Keywords: Auditing; Auditor Nurse; Health plan.